Characterization of MSP1 Promoter and Identification of Transcription Factors Involved in Regulation of Abscisic Acid- and Ethylene-Responsive Gene Expression in Oil Palm - Omidvar, Vahid (2011)
The 1,053-bp promoter of the oil palm metallothionein gene (so-called MSP1) and its 5´ deletions were analyzed in transiently transformed oil palm tissues. The full length promoter showed 7-fold higher activity in the mesocarp than in leaves and 1.5-fold more activity than the CaMV35S promoter in the mesocarp. Two positive regulatory regions at nucleotides (nt) -953 to -619 and -420 to -256 regions and a negative regulatory region at -619 to -420 nt region were identified within the promoter sequence. Fine-tune deletion analysis of the -619 to -420 nt region led to the identification of a novel negative regulatory AGTTAGG core-sequence, responsible for controlling the fruit-specific activity of the MSP1promoter. Abscisic acid (ABA) and copper (Cu2+) induced the activity of the promoter and its 5´ deletions more effectively than methyl jasmonate (MJ) and ethylene. Regulatory DNA motifs responsive to ABA, copper, MJ, and ethylene were identified within the promoter sequence. These results suggest that the MSP1 promoter and its regulatory regions are potentially useful for engineering fruit-specific and inducible gene expression in oil palm. ABF family of transcription factors (TFs) play important regulatory roles in plant response to abiotic stresses as well as plant growth and development. Two ABA-responsive cDNA clones, named EABF and EABF1 were isolated from oil palm fruits using yeast one-hybrid system. EABF had a conserved AP2/EREBP DNA-binding domain (DNA-BD) and a potential nuclear localization sequence (NLS). No previously known DNA-BD was identified from the EABF1 sequence. EABF and EABF1 proteins were classified as DREB/CBF and bZIP family members based on the multiple sequence alignment and phylogenetic analysis. Both proteins showed ABRE-binding and transcriptional activation properties in yeast. Furthermore, both proteins were able to trans-activate the down-stream expression of the LacZ reporter gene in yeast. EABF was induced in response to ABA in oil palm fruits and leaves, but not in roots, while expression of EABF1 was constitutively induced in all tissues. The expression of both genes were strongly induced in fruits in response to ABA, ethylene, MJ, drought, cold and high-salinity treatments, indicating that EABF and EABF1 might act as connectors among different signal transduction pathways. Our current results suggest that EABF and EABF1 are involved in abiotic stress response and ABA signaling in oil palm. AP2/ERF family of TFs are involved in plant response to various biotic and abiotic stresses and also regulate many aspects of plant growth and development, such as flowering control and fruit ripening. Two ethylene-responsive cDNA clones designated EgEREBP and EgAP2-1were isolated from oil palm fruits. EgEREBP had a conserved AP2/EREBP DNA-BD and a potential NLS and was similar to DREB/CBF subfamily of AP2/ERFs. EgAP2-1 contained two AP2/EREBP domains and classified as AP2 subfamily member of AP2/ERFs. Both proteins showed ERE binding, transcriptional activation, and transactivation properties in yeast and in vitro. EgEREBP had a very basal expression in fruits, leaves and roots, while the expression of EgAP2-1 was found to be developmentally-regulated in ripening fruits, but not in leaves and roots. EgEREBP was induced in response to a range of hormone treatments and abiotic stresses, while EgAP2-1 was only induced in response to ethylene and ABA, but not other hormones and not to abiotic stresses as well. These observations imply the regulatory function of EgEREBP in plant response to biotic and abiotic stresses, while EgAP2-1 is involved in ethylene and/or ABA signaling pathways and perhaps might have a regulatory function more towards fruit-ripening control rather than the stress response in plant. Taken together, our studies have provided valuable information on the transcriptional regulatory mechanisms in oil palm for specific and inducible expression in fruits and stress responses involving specific interaction of transcription factors and regulatory motifs which are essential for future genetic improvement efforts.